Internal combustion engine handbook basics, components, systems, and perspectives - Van Basshuysen, Richard, 1932-; Schäfer, Fred, 1948- (Society of Automotive Engineers, 2004)
Thorough in its presentation, this essential resource illustrates the latest level of knowledge in engine development, paying particular attention to the presentation of theory and practice in a balanced ratio. Almost 950 pages in length - with 1,250 illustrations and nearly 700 bibliographical references - the Internal Combustion Engine Handbook covers all of this component's complexities, including an insightful look into the internal combustion engine's future viability.
Title from PDF title page (SAE Web site, 08/15/2012).
Keywords: Internal combustion engines.; elektronické knihy; electronic books